How about an extensive reading guidebook? A case study in a higher education - Rahmawati, Henny; Nurisma, Radina Anggun (Politeknik Negeri Bali, 2023)
This study was aimed at investigating the lecturers’ need of a guidebook in the ER enactment within a classroom. The method used in this study was a qualitative research method making use of an online questionnaire and a semi-structured interview as the instruments to compile the data. The participants of this study were six lecturers implementing Extensive Reading in their classroom, three of whom are seniors, and the other three are novice lecturers. The data compiled from an online questionnaire and a semi-structured interview were then qualitatively analyzed and discussed. The result showed that an ER guidebook is, indeed, needed by those who are still lacking of experience in teaching extensive reading in which the contents are about choosing the appropriate books, accessing online repository, conducting ER, ER fun activities, and the potential evaluation, but it is not that urgent though it benefits to some cases for those who have been the so-called ER expert having years of experiences—more than two years—teaching extensive reading at class. However, using extensive reading guidebook might be a stimulus, for both lecturers in teaching, which is still open to innovative teaching invention in teaching extensive reading.